Розсiяння флюксона на полосоподiбнiй домiшцi у двовимiрному джозефсонiвському переходi - Starodub, I. O.; Zolotaryuk, Y. (Publishing house "Academperiodika", 2018)
The interaction of a soliton (fluxon) with a stripe-like inhomogeneity in a two-dimensional Josephson junction is studied. The radiation emitted due to the fluxon scattering on the impurity is calculated. The total radiation energy shows a distinct resonant dependence as a function of the fluxon velocity. The current-voltage characteristic of such a junction with a fluxon trapped in it is calculated. The signature of the emitted radiation on the current-voltage dependence is analyzed.